SURG-03. COMBINATION LASER INTERSTITIAL THERMAL THERAPY PLUS SRS INCREASES TIME TO PROGRESSION FOR RECURRENT SRS-TREATED BRAIN METASTASES. (9th November 2020) - Grabowski, Matthew; Sankey, Eric; Srinivasan, Ethan; Otvos, Balint; Scott, Alex; Olufawo, Michael; Kim, Albert; Leuthardt, Eric; Barnett, Gene; Mohammadi, Alireza; Fecci, Peter
Abstract: INTRODUCTION: Laser interstitial thermal therapy (LITT) has evolved as an effective treatment for brain metastases (BM) failing stereotactic radiosurgery (SRS), and an alternative to open resection/repeat SRS. We sought to evaluate the efficacy of LITT+SRS in recurrent SRS-treated BM, and compare outcomes to LITT alone vs. repeat SRS. METHODS: A multicenter, retrospective study was performed of patients with biopsy-proven BM recurrence after SRS. Patients were stratified by planned LITT+SRS vs. LITT alone vs. repeat SRS. Index lesion progression was determined by RANO criteria. RESULTS: Forty-five patients fit inclusion, with a median follow-up of 7.3 months (range:1.1-30.5), age of 60 (range:37-86), KPS of 80 (range:60-100), and contrasted tumor volume (CTV) of 6.1cc (range:1.4-19.4). Histologies included NSCLC (44%), breast (24%), SCLC, melanoma, colon, and oroesophageal (< 10% each). Sixty-three percent of patients underwent LITT alone, 18% had repeat SRS, while 27% had LITT+SRS (post-LITT SRS). Median time to index lesion progression was greatest in the LITT+SRS group compared to LITT alone or repeat SRS (>23, 7.5, and 3.6 months, respectively [p=0.018]), as was overall survival (23.7, 5.9, and 7.0 months, respectively [p=0.023]). Age, sex, primary histology, CTV, and treatment strategy were univariate predictors of tumor progression; patients not treated with LITT+SRS were more likely to have index lesion progression (p=0.016). When controlling for histology and CTV in a multivariate model, patients not treated with LITT+SRS were significantly more likely to have progression (p=0.001). All LITT+SRS patients who experienced subsequent radiographic progression were diagnosed with recurrent tumor, while radiation necrosis incidence in the repeat SRS arm was 25%. CONCLUSION: LITT+SRS appears superior to LITT alone or repeat SRS for treatment of biopsy-proven BM recurrence after SRS when controlling for other variables known to be predictive of progression. Prospective trials should be designed to validate the utility of combination LITT+SRS after SRS failure.